طبيعة القواعد الدستورية وضمانات تطبيقها - الزهيري، أبو بكر مرشد فازع (الجمعية المصرية للاقتصاد السياسي والإحصاء والتشريع, 2018)
This research discusses the Elis agreement among legal jurisprudence on the nature of constitutional rules weather they are legal rules or merely ethical rules of conduct. The disagreement is mainly based on the extent and degrees of sanction that related to these rules compared with other rules, which clearly encompass this element. The impacts and consequences or this disagreement is one of the main issue of this study. Emphasis has been given to the nature of the sanction resulting due to the violation of the constitutional rules which is considered, according to the researcher opinion, to be closer to the guarantees for the application of such rules.
Keywords: القوانين والتشريعات -- القواعد الدستورية -- حقوق الإنسان -- الضمانات الدستورية